2001
DOI: 10.2134/jeq2001.302493x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Diammonium Phosphate to Reduce Heavy Metal Solubility and Transport in Smelter‐Contaminated Soil

Abstract: Phosphate treatments can reduce metal dissolution and transport from contaminated soils. However, diammonium phosphate (DAP) has not been extensively tested as a chemical immobilization treatment. This study was conducted to evaluate DAP as a chemical immobilization treatment and to investigate potential solids controlling metal solubility in DAP-amended soils. Soil contaminated with Cd, Pb, Zn, and As was collected from a former smelter site. The DAP treatments of 460, 920, and 2300 mg P kg-1 and an untreated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(102 citation statements)
references
References 36 publications
4
94
0
4
Order By: Relevance
“…4). In addition to an increase in soil pH, P entering into soil with biochar application (especially RBC) may also have been a contributing factor in immobilizing Cd, Zn, and Pb via the formation of phosphate precipitates (McGowen et al 2001;Tang et al 2004) and activating As via competing adsorption onto soil surface with arsenate (Jain and Loeppert 2000). Arsenate retained in soil particles can be desorbed by phosphate and released into soil solution.…”
Section: Discussionmentioning
confidence: 99%
“…4). In addition to an increase in soil pH, P entering into soil with biochar application (especially RBC) may also have been a contributing factor in immobilizing Cd, Zn, and Pb via the formation of phosphate precipitates (McGowen et al 2001;Tang et al 2004) and activating As via competing adsorption onto soil surface with arsenate (Jain and Loeppert 2000). Arsenate retained in soil particles can be desorbed by phosphate and released into soil solution.…”
Section: Discussionmentioning
confidence: 99%
“…From Eqns 1 and 2 it can be seen that the two models had a high coefficient of determination (R 2 ) and a small standard error of the estimate (SE), which means the chemical transformation of Cd in calcareous soil treated with the two P-containing acidify agents was mainly associated with the addition level of P in water-soluble form and not soil pH. However, several studies have reported that water-soluble phosphate compounds can immobilise Cd through various mechanisms, such as surface complexation, ion exchange, precipitation and adsorption (LeviMinzi and Petruzzelli 1984;Pearson et al 2000;McGowen et al 2001;Bolan et al 2003;Thawornchaisit and Polprasert 2009). …”
Section: Chemical Transformation Of CDmentioning
confidence: 99%
“…Organic contaminants are generally accepted to undergo microbiological breakdown, but mineral ones, specifically heavy metals, may affect the environment for long periods since they are not biodegradable. Soils and their heterogenic nature (mineral and organic colloids) create in many cases favorable conditions for the mitigation of the harmful effects of heavy metals (McBride et al 1997;Mench et al 1998;Basta, McGowen 2004). This process may last for extended periods of time estimated at decades, hundreds or even thousands of years, depending on the soil conditions and the concentrations of anthropogenic heavy metals (Sparks 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Several remediation methods have been applied under in-situ (Matsi, Keramidas 1999;McGowen 2000;Oste et al 2002) as well as ex-situ (Tandy et al 2004;Diatta, Chudzinska 2009) conditions to soils anthropogenically contaminated with various contaminants. Additives, among others zeolites (Querol et al 2005) and clay minerals (Lombi et al 2003), were also applied to soils for this purpose.…”
Section: Introductionmentioning
confidence: 99%